Determination of brain tumor recurrence using 11C‐methionine positron emission tomography after radiotherapy. Issue 10 (13th August 2021) - Yamaguchi, Shigeru; Hirata, Kenji; Okamoto, Michinari; Shimosegawa, Eku; Hatazawa, Jun; Hirayama, Ryuichi; Kagawa, Naoki; Kishima, Haruhiko; Oriuchi, Noboru; Fujii, Masazumi; Kobayashi, Kentaro; Kobayashi, Hiroyuki; et al.
Abstract: We conducted a prospective multicenter trial to compare the usefulness of 11 C‐methionine (MET) and 18 F‐fluorodeoxyglucose (FDG) positron emission tomography (PET) for identifying tumor recurrence. Patients with clinically suspected tumor recurrence after radiotherapy underwent both 11 C‐MET and 18 F‐FDG PET. When a lesion showed a visually detected uptake of either tracer, it was surgically resected for histopathological analysis. Patients with a lesion negative to both tracers were revaluated by magnetic resonance imaging (MRI) at 3 months after the PET studies. The primary outcome measure was the sensitivity of each tracer in cases with histopathologically confirmed recurrence, as determined by the McNemar test. Sixty‐one cases were enrolled, and 56 cases could be evaluated. The 38 cases where the lesions showed uptake of either 11 C‐MET or 18 F‐FDG underwent surgery; 32 of these cases were confirmed to be subject to recurrence. Eighteen cases where the lesions showed uptake of neither tracer received follow‐up MRI; the lesion size increased in one of these cases. Among the cases with histologically confirmed recurrence, the sensitivities of 11 C‐MET PET and 18 F‐FDG PET were 0.97 (32/33, 95% confidence interval [CI]: 0.85‐0.99) and 0.48 (16/33, 95% CI: 0.33‐0.65), respectively, and the difference was statistically significant ( P  < .0001). The diagnostic accuracy of 11 C‐MET PET was significantly better than that of 18 F‐FDG PET (87.5% vs. 69.6%, P  = .033). No examination‐related adverse events were observed. The results of the study demonstrated that 11 C‐MET PET was superior to 18 F‐FDG PET for discriminating between tumor recurrence and radiation‐induced necrosis. Abstract : This prospective multicenter study using positron emission tomography (PET) demonstrated the uptake of 11 C‐methionine at a significantly higher sensitivity with brain tumor recurrence after radiotherapy than that of 18 F‐fluorodeoxyglucose, based on histopathological evidence. The 11 C‐methionine PET can be a useful diagnostic tool for the detection of tumor recurrence, distinguishable from radiation‐induced necrosis after radiotherapy in brain tumors.